(untitled) (Research, Society and Development, 2022)
The present work aimed to describe the performance of the managing body of the state of Pará in the implementation of forest concessions; based on the monitoring of forest concession contracts in public forests known as the Mamuru-Arapiuns Group of Glebas and Paru State Forest. The studies were carried out in public forests, in the state of Pará, in the mesoregion of Baixo Amazonas, in 09 forest concession contracts. This research was based on bibliographic and documental instruments, based on scientific papers and official documents provided by the Institute of Forestry and Biodiversity Development. Among the main results we have the pioneering role of the state of Pará as the only federative entity to implement forest concessions in non destined forests or type B forests, since the creation of the public forest management law. For the effective management and monitoring, the managing body has endeavored in the elaboration of norms, guidelines, technical notes, technical opinions that aim to guide the concessionaires to the fulfillment of the forest concession contracts. In general, even in the face of numerous adverse situations, IDEFLOR-Bio’s performance in the management has the purpose of guaranteeing that the forest concession is maintained as an effective and efficient forest policy.